New ways of diabetes management with smart data and genomic data - Becker Kurt (Current Directions in Biomedical Engineering, 2017)
By 2025, the number of diabetic patients worldwide could rise by more than 50 percent from now 250 million to about 380 million. With about 6 million patients, diabetes mellitus is one of the greatest national diseases in Germany.